2020
DOI: 10.1051/0004-6361/201937057
|View full text |Cite
|
Sign up to set email alerts
|

A new fitting function for GRB MeV spectra based on the internal shock synchrotron model

Abstract: Aims. The physical origin of the gamma-ray burst (GRB) prompt emission is still a subject of debate. Internal shock models have been widely explored, owing to their ability to explain most of the high-energy properties of this emission phase. While the Band function or other phenomenological functions are commonly used to fit GRB prompt emission spectra, we propose a new parametric function that is inspired by an internal shock physical model. We use this function as a proxy of the model to compare it easily t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…However, recent studies show that the Band function is a poor model for the physical emission spectra (e.g., Burgess et al (2015), Burgess et al (2019a), Zhang et al (2019b) ) and should only be used as a qualitative description of the spectra such as the peak energy and flux. However, Yassine et al (2019) also show that the Band function may not adequately model the true peak energy either. The use of physical models to perform the analysis, as in Burgess et al (2019b), would be preferable to avoid overinterpretation of the spectral parameters found using empirical models.…”
Section: Catalog Analysismentioning
confidence: 96%
“…However, recent studies show that the Band function is a poor model for the physical emission spectra (e.g., Burgess et al (2015), Burgess et al (2019a), Zhang et al (2019b) ) and should only be used as a qualitative description of the spectra such as the peak energy and flux. However, Yassine et al (2019) also show that the Band function may not adequately model the true peak energy either. The use of physical models to perform the analysis, as in Burgess et al (2019b), would be preferable to avoid overinterpretation of the spectral parameters found using empirical models.…”
Section: Catalog Analysismentioning
confidence: 96%
“…In this analysis, threeML offered the full accuracy of the LAT unbinned likelihood technique, which is lost during the binning in space and energy that is required by pyXSPEC. We considered the spectral models Band [5] and ISSM [6], both having four parameters. Additionally, we considered the models obtained by multiplying these functions by a high-energy exponential cutoff (∝ 𝑒 −𝐸/𝐸 𝑐𝑢𝑡 ).…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…This may become a problem in instances where such models are unable to capture the intrinsic complexity of the underlying data. Therefore, an arguably better approach is to directly fit physical models to the raw data to derive spectral parameters and remove any bias [103][104][105][106]. Such an approach has led to alleviating some of the issues encountered by the optically thin synchrotron model, where it was shown that direct spectral fits (in count space rather than energy space) with synchrotron emission from cooling power-law electrons can explain the low-energy spectral slopes as well as the spectral width of the peak [107].…”
Section: Optically-thin Synchrotron Emissionmentioning
confidence: 99%